2017
DOI: 10.1177/0263617417721588
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a novel CeO2/SiO2 adsorbent and its adsorption behavior for fluoride ion

Abstract: The silica-based CeO 2 adsorbent (CeO 2 /SiO 2) was prepared for removing fluoride from the aqueous solution. The synthesized adsorbent was characterized by scanning electron microscope, energy dispersive spectrum, X-ray diffractometer, Fourier transform infrared spectrometer, and zeta potential measurement analyses. The adsorption batch experiments in the various experimental conditions including solution pH, contact time, initial fluoride concentration, and adsorption temperature were performed and investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Metal oxides have great potential for adsorption, favorable safety, minimal water solubility, and a benecial capacity for desorption, making them suitable materials. Some of them are magnetic iron-aluminum oxide/graphene oxide nanoparticles, 21 hydrous iron oxide incorporating cerium, 3 Ce-Zr oxide nanosphere-encapsulated calcium alginate beads, 22 ironaluminum nanocomposites, 23 aluminium oxide nanoparticles, 24,25 nanoscale aluminium oxide hydroxide, 26 magnetic core-shell Ce-Ti@Fe 3 O 4 nanoparticles, 27 hydroxyapatite montmorillonite nanocomposites, 28 2-line ferrihydrite, 29 cupric oxide nanoparticles, 30 CeO 2 /SiO 2 , 31 Ce-Zn binary metal oxides, 32 and superparamagnetic zirconia nanomaterials (ZrO 2 /SiO 2 /Fe 3 O 4 ). 33 However, the removal of uoride by these materials has resulted in low adsorption capacities (i.e., as low as 0.2 mg g À1 ) with long contact duration of more than 24 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxides have great potential for adsorption, favorable safety, minimal water solubility, and a benecial capacity for desorption, making them suitable materials. Some of them are magnetic iron-aluminum oxide/graphene oxide nanoparticles, 21 hydrous iron oxide incorporating cerium, 3 Ce-Zr oxide nanosphere-encapsulated calcium alginate beads, 22 ironaluminum nanocomposites, 23 aluminium oxide nanoparticles, 24,25 nanoscale aluminium oxide hydroxide, 26 magnetic core-shell Ce-Ti@Fe 3 O 4 nanoparticles, 27 hydroxyapatite montmorillonite nanocomposites, 28 2-line ferrihydrite, 29 cupric oxide nanoparticles, 30 CeO 2 /SiO 2 , 31 Ce-Zn binary metal oxides, 32 and superparamagnetic zirconia nanomaterials (ZrO 2 /SiO 2 /Fe 3 O 4 ). 33 However, the removal of uoride by these materials has resulted in low adsorption capacities (i.e., as low as 0.2 mg g À1 ) with long contact duration of more than 24 hours.…”
Section: Introductionmentioning
confidence: 99%
“…This was explained with the equations given in Table 1, then the isotherm constants were calculated with the slopes of the curves and the y-intercept of the equations. In these equations, Ce indicated metal concentration at equilibrium (mg/L); = was the amount of adsorbed metal ion by the adsorbent (mg/g) [28,[39][40][41].…”
Section: Effect Of Initial Cr(vi) Concentration On the Adsorption Promentioning
confidence: 99%
“…The effect of temperature on the adsorption of Cr(VI) ions was investigated and the adsorption capacity was calculated as higher at low temperatures for BC composite capsules. By using Van't Hoff equation, a graph of log Kc vs. 1/T was drawn, standard free energy (G), enthalpy (H) and entropy (S) changes were calculated [40].…”
Section: Adsorbent Adsorption Capacity (Mg/g) Referencesmentioning
confidence: 99%
“…However, reports showed that traditional carbons could not remove As and F due to its lower adsorption capacity (Rojas‐Mayorga, Bonilla‐Petriciolet, Silvestre‐Albero, Aguayo‐Villarreal, & Mendoza‐Castillo, ; Velazquez‐Jimenez, Arcibar‐Orozco, & Rangel‐Mendez, ). Adsorbent functionalized with aluminum, cerium, lanthanum and zirconium are more capable of removing contaminants (He et al, ; Lin, Wu, Khayambashi, Wang, & Wei, ; Te, Wichitsathian, Yossapol, & Wonglertarak, ). Some special characteristics such as surface area, porosity and the presence of functional groups enhanced the adsorption properties (Arcibar‐Orozco, Josue, Rios‐Hurtado, & Rangel‐Mendez, ).…”
Section: Removal Of Arsenic and Fluoride From Contaminated Water/raw mentioning
confidence: 99%